Idiopathic pulmonary fibrosis: diagnostic pitfalls and therapeutic challenges - Spagnolo Paolo; Tonelli Roberto; Cocconcelli Elisabetta; Stefani Alessandro; Richeldi Luca (Multidisciplinary Respiratory Medicine, 2012)
Abstract Idiopathic pulmonary fibrosis (IPF), the most common of the idiopathic interstitial pneumonias, is a devastating condition that carries a prognosis worse than that of many cancers. As such, it represents one of the most challenging diseases for chest physicians. The diagnostic process is complex and relies on the clinician integrating clinical, laboratory, radiologic, and/or pathologic data. Therefore, a close collaboration between chest physicians, radiologists, and pathologists experienced in the diagnosis of interstitial lung diseases (ILDs) is necessary in order to minimize diagnostic uncertainty. Similarly, the management of IPF continues to pose major difficulties. However, while there are no proven effective therapies for IPF beyond lung transplantation, recent trials of novel agents suggest that pharmacological treatment may retard the progression of the disease. In this regard, enrolment of patients into clinical trials is considered the “best current practice”by the most recent guidelines as it offers IPF patients the chance to receive new agents that may be more effective than current therapies. A more recent trend focusing on improving quality of life in IPF patients has also been gaining ground. The diagnosis and management of IPF remains a constant challenge for even the most experienced of clinicians. However, a multidisciplinary approach to this complex disease is steadily improving diagnostic accuracy, while recent advances in the pharmacological therapy offer the genuine promise of future treatments for this devastating disease.